#TITLE_ALTERNATIVE# - ADITIAWATI, PINGKAN
Present study concerns the preliminary investigation to obtain optimal conditions for the use of immobilized E. coli cells in the process of the bioconversion of penicillin G to 6-APA. 5 E. coli strains which comprise the collection of the Microbiology and Fermentation Technology Laboratorium of the Department of Chemical Engineering were studied as to determine the most active strain for the purpose mentioned. The selection was done by comparing its growth on a medium containing 0,1%, 0,5%, 1% and 2% penicillin G respectively. It was found that strain number 2 was the most active one. Optimal conditions of the E. coli cells for this purpose were made by growing E. coli 2 in various growth medium i.e nutrient broth, Devic & Divjak's medium and Kaufman & Bauer medium. Good growth was observed in nutrient broth. For the same purpose optimal environmental conditions on various production medium were studied. The initial pH (7,0; 7,5; 8,0 and 8,5) and several incubation temperatures (25oC, 35oC and 40oC) were observed by using of Sato T's, Tosa T's and Chibata I medium. The initial pH 7,5 and incubation temperature 40oC gave the results. The conditions for immobilized the E. coli cells for optimal bioconversion was observed when a solution of Na-reginate 2% and silica 2% was used producing particles of 2-3 mm. The bioconversion process itself was done by using a fluidized column. For this purpose the minimal velocity of the fluid should be determined to keep the immobilized cell fluidized. This was observed at a velocity 5 ml/second. The enzyme activities of the whole and immobilized cells were determined by the production of 6-APA. It was found that whole cells convert 15 mM penicillin G as much as 12 umol/ml in 22 hours, while immobilized cells convert only slightly lower i.e. 13 umol/ml in 3 hours. Last but not least the velocity of the fluid containing the substrate (penicillin G) was determined by varying the velocity : 5 ml/second, 10 ml/second and 15 ml/second. The speed of 10 ml/second gave the best result.